The Effect of the PjBL-STEM Model on Students' Critical Thinking Ability in Science Learning - Herlita, Fintya; Yamtinah, Sri; Wati, Icha Kurnia (Jurnal Inovasi Pendidikan IPA, 2023)
This study aims to prove the effectiveness of the PjBL-STEM model on students' critical thinking ability in science learning. This research is a quasi-experimental study with a pretest-posttest control group design. The experimental class in this research received the treatment of the PjBL-STEM model, and the control class received the treatment of the PjBL model. The research population was class VIII students of SMP Negeri 1 Dukun for the 2022/2023 academic year, which consisted of six classes. Meanwhile, the research sample was selected using a cluster random sampling technique, with class VIII E as the experimental class and class VIII F as the control class. This research data is the difference in pretest-posttest scores (gain scores) of students' critical thinking ability, which was analyzed by the right-sided t-test. The results of the independent sample t-test showed tcount>ttable (4.012>1.669) and Pvalue<0.05 (0.000<0.05), which means the test decision is H0 is rejected. So, it can be proven that the effect of the PjBL-STEM model on students' critical thinking skills in science learning is greater than the control class, which is supported by the N-gain value in the experimental class of 0.417 (medium) and control class of 0.246 (low).